(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2019)
A total of 11 bee species belonging to two families Apidae and Megachilidae was identified. The identified species were Apis dorsata, Apis mellifera, Apis cerana, Apis florea, Ceratina binghami, Ceratina nigrolateralis, Xylocopa aestuans, Xylocopa violacea, Xylocopa latipes, Megachile disjuncta and Megachile umbripennis. The species were identified by using standard taxonomic keys. Details of external morphology like head, wing venation, antennal type, physical coloration etc. were used in the keys. The bees were collected from three areas of Dhaka city - Curzon Hall, Ramna Park and Sher-e-Bangla Agricultural University from October 2017 to May 2018. During the study period it was observed that the richness of bee species was found maximum during the month of October (31.01%) and was more abundant in Curzon Hall and Sher-e-Bangla Agricultural University area than the Ramna park area. The bee A. dorsata was the most abundant (about 36.23% of the total population) and M. umbripennis was the least abundant (about 1.74% of the total population) species in the study areas. It was also observed that bee species were more attracted to the yellow flowers specially Cosmos sulphureus and Tecoma stans than the other coloured flowers. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(1): 113-120